1989
DOI: 10.1093/ajcn/50.3.607
|View full text |Cite|
|
Sign up to set email alerts
|

Putative biological mechanisms of the effect of iron deficiency on brain biochemistry and behavior

Abstract: An animal model of nutritional iron deficiency (ID) is described that demonstrates a reduction of brain nonheme iron. The most prominent feature of ID is the significant and selective diminution of central dopamine neurotransmission resulting from the decreased number of dopamine D2 receptors in the caudate nucleus, nucleus accumbens, pituitary, and in all probability the frontal cortex. The consequences of diminished dopaminergic neurotransmission is a modification of dopamine-dependent behaviors and biochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
135
0
2

Year Published

1991
1991
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(149 citation statements)
references
References 2 publications
12
135
0
2
Order By: Relevance
“…These decrement in enzyme activities ~ncrease with the duration of low iron intake. The brain concentration of GABA was also found to reduce, which may be because of altered metabolism of GABA during iron deficiency anemia in coroboration with the earlier studies (7). Hill eta/ (19) suggested that there is a great similarity in the brain iron distribution and brain regions that receive inputs from GABA.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…These decrement in enzyme activities ~ncrease with the duration of low iron intake. The brain concentration of GABA was also found to reduce, which may be because of altered metabolism of GABA during iron deficiency anemia in coroboration with the earlier studies (7). Hill eta/ (19) suggested that there is a great similarity in the brain iron distribution and brain regions that receive inputs from GABA.…”
Section: Discussionsupporting
confidence: 65%
“…It has been proposed that alteration in dopamme, 5HT (Serotonin) receptors that follow tron deficiency, mediate through the neuro developmental changes. Early iron deficiency has also been shown to affect GABA metabolism in adult rats (7,8).…”
Section: Indian Journal Of Clinicalmentioning
confidence: 99%
“…The homeostasis of brain iron is thought to be necessary for normal brain function, especially in learning and memory (Youdim et al 1989). iron-chelating agent (HLA20) and also with the iron-chelator VK-28 (data not shown), ironchelation seems to be crucial for the cognitive improvement effect of M30 in this model.…”
mentioning
confidence: 80%
“…Among these, surprisingly, memory disorders appeared as significantly less frequent in women with serum ferritin concentrations below 15 mg/l, or even more so, below 10 mg/l. Others demonstrated that, in rodents, iron deficiency without anemia protected against the neurodegeneration of specific cerebral zones, in particular, the hippocampus zone (Hallberg & Asp, 1996), one of the memory zones (Bohbot et al, 2000), whereas subjects with iron-deficient anemia presented more frequently with memory loss because of major alterations of enzymatic reactions of the serotonin metabolism (mitochondrial aldehyde oxidase) or of catecholamines catabolism (mitochondrial monoamine oxidase) within the neuronal mitochondria, leading to a cerebral storage of triptaminergic derivatives and of catecholamines (adrenaline, noradrenaline and dopamine) (Youdim et al, 1983(Youdim et al, , 1989Hallberg & Asp, 1996;Youdim & Yehuda, 2000;Erikson et al, 2001). …”
Section: Discussionmentioning
confidence: 99%